Toward Vision 2020: Organisational Learning Practices in Malaysia - Arshad, M.; Scott-Ladd, Brenda (International Employment Relations Association, 2010)
The Malaysian Government has adopted organisational learning as a key strategy to assist the country achieve its Vision 2020. This paper reports on a study that investigated the organisational learning strategies practised in Malaysian organisations across four key industries: government, manufacturing, health and academic. Western authors define organisational learning as a process of knowledge acquisition that involves continuous change to create, acquire and transfer knowledge (Garvin 1993; Miller 1996; Williams 2001). The study sought to determine the extent of learning strategies currently being implemented to obtain and transfer knowledge, as well as assess further opportunities for take-up of learning strategies. Thirty-five managers, government officials and academics participated in in-depth interviews in 2004. Data was transcribed manually, and then interrogated using NVivo software to explore similarities and differences within and between the sectors. The findings suggest Malaysian organisations which are implementing organisational learning strategies prefer active and cooperative learning strategies that are delivered through structured training and development programs.